1989
DOI: 10.1126/science.2781297
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Marine Bacteria Chemically Defend Crustacean Embryos from a Pathogenic Fungus

Abstract: Embryos of the shrimp Palaemon macrodactylus are remarkably resistant to infection by the fungus Lagenidium callinectes, a recognized pathogen of many crustaceans. An Alteromonas sp. bacterial strain consistently isolated from the surface of the embryos, produces 2,3-indolinedione (isatin), a compound that inhibits the pathogenic fungus. If exposed to the fungus, bacteria-free embryos quickly die, whereas similar embryos reinoculated with the bacteria or treated only with 2,3-indolinedione live well. The comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
237
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(241 citation statements)
references
References 16 publications
3
237
0
1
Order By: Relevance
“…Feifarek (1987) described how an epibiotic sponge impeded starfish predation on a spiny oyster, Barkai & McQuaid (1988) found that whelks in shells overgrown by a bryozoan were resistant to lobster predation, and Gil-Turnes et al (1989) reported that bacteria growing on the surface of shrimp embryos chemically defended the embryos from pathogenic fungi. Bach (1980) mentioned how normally immune corn may be moderately attacked by cucumber herbivores when grown intermixed with cucumber, Threlkeld et al (1993) found that zooplankton may become more susceptible to predation when fouled, and epibiotic bryozoans have been shown to increase the attractiveness of kelp blades for grazing fishes (Bernstein & Jung, 1979) and echinoids (Ryland, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Feifarek (1987) described how an epibiotic sponge impeded starfish predation on a spiny oyster, Barkai & McQuaid (1988) found that whelks in shells overgrown by a bryozoan were resistant to lobster predation, and Gil-Turnes et al (1989) reported that bacteria growing on the surface of shrimp embryos chemically defended the embryos from pathogenic fungi. Bach (1980) mentioned how normally immune corn may be moderately attacked by cucumber herbivores when grown intermixed with cucumber, Threlkeld et al (1993) found that zooplankton may become more susceptible to predation when fouled, and epibiotic bryozoans have been shown to increase the attractiveness of kelp blades for grazing fishes (Bernstein & Jung, 1979) and echinoids (Ryland, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Crustacean and squid embryos harbor symbiotic bacteria on the egg surface or in embryo sheaths. In the shrimp Palaeomon macrodactylus, symbiotic Alteromonas produce indolinedione, which protects the embryo from fungal infections (11). In squid, bacteria live as symbionts in the adult accessory nidamental gland, and the bacteria are secreted onto the egg jelly and chorion at spawning (12).…”
Section: Protective Strategies Independent Of Developmental Programsmentioning
confidence: 99%
“…Treatment of the embryos by antibacterial agents inhibited the growth of the bacteria, but all the embryos died from infec- tion by the fungus Lagenidium callinectes. In fact, the bacterial metabolite isatin protects the shrimp embryos against fungal overgrowth (Gil-Turnes et al 1989). Dibromotyrosines are common metabolites from Aplysina sponges (Minale et al 1976) that have been proposed as chemotaxonomic markers of the order Verongida (Berquist and Wells 1983).…”
Section: Resultsmentioning
confidence: 99%